Tissue‐Engineered Fibrin‐Based Heart Valve with Bio‐Inspired Textile Reinforcement. Issue 16 (5th July 2016) - Moreira, Ricardo; Neusser, Christine; Kruse, Magnus; Mulderrig, Shane; Wolf, Frederic; Spillner, Jan; Schmitz‐Rode, Thomas; Jockenhoevel, Stefan; Mela, Petra
Abstract : The mechanical properties of tissue‐engineered heart valves still need to be improved to enable their implantation in the systemic circulation. The aim of this study is to develop a tissue‐engineered valve for the aortic position – the BioTexValve – by exploiting a bio‐inspired composite textile scaffold to confer native‐like mechanical strength and anisotropy to the leaflets. This is achieved by multifilament fibers arranged similarly to the collagen bundles in the native aortic leaflet, fixed by a thin electrospun layer directly deposited on the pattern. The textile‐based leaflets are positioned into a 3D mould where the components to form a fibrin gel containing human vascular smooth muscle cells are introduced. Upon fibrin polymerization, a complete valve is obtained. After 21 d of maturation by static and dynamic stimulation in a custom‐made bioreactor, the valve shows excellent functionality under aortic pressure and flow conditions, as demonstrated by hydrodynamic tests performed according to ISO standards in a mock circulation system. The leaflets possess remarkable burst strength (1086 mmHg) while remaining pliable; pronounced extracellular matrix production is revealed by immunohistochemistry and biochemical assay. This study demonstrates the potential of bio‐inspired textile‐reinforcement for the fabrication of functional tissue‐engineered heart valves for the aortic position. Abstract : A tissue‐engineered heart valve able to withstand the systemic circulation in vitro is produced by exploiting the mechanical strength and anisotropy of a bio‐inspired textile composite scaffold. The design addresses major limitations of current concepts, specifically (i) the inadequate mechanical properties for the aortic position, (ii) the lack of scaffold anisotropy, and (iii) the mechanically critical wall‐leaflet junction.